Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/eye.2016.54
|View full text |Cite
|
Sign up to set email alerts
|

The increase of aqueous tear volume by diquafosol sodium in dry-eye patients with Sjögren’s syndrome: a pilot study

Abstract: Purpose To investigate the effect of 3% diquafosol sodium ophthalmic solution (DQS) on aqueous tear volume increase in dry-eye patients with Sjögren's syndrome (SS). Methods In this pilot study, 17 dry-eye patients with SS (1 male and 16 females; mean age: 66.4 years) were enrolled and underwent topical instillation of two ophthalmic solutions, artificial tears (AT) in one eye and DQS in the fellow eye, in a masked manner. The central lower tear meniscus radius (TMR) curvature was measured before and at 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
19
0
1
Order By: Relevance
“…Kim et al reported that a cyclosporine treatment group also used artificial tears to reduce symptoms of Meibomian gland dysfunction [21]. Diquafosol treatment groups also used artificial tears to inhibit DED symptoms [10,12,21,22]. In short, neither cyclosporine nor diquafosol were solely adequate for the treatment of moderate or severe DED.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a cyclosporine treatment group also used artificial tears to reduce symptoms of Meibomian gland dysfunction [21]. Diquafosol treatment groups also used artificial tears to inhibit DED symptoms [10,12,21,22]. In short, neither cyclosporine nor diquafosol were solely adequate for the treatment of moderate or severe DED.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a cyclosporine treatment group also used artificial tears to reduce symptoms of Meibomian gland dysfunction [23]. Diquafosol treatment groups also used artificial tears to inhibit DED symptoms [11,13,23,24]. In short, neither cyclosporine nor diquafosol were solely adequate for the treatment of moderate or severe DED.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that a cyclosporine treatment group also used artificial tears to reduce symptoms of Meibomian gland dysfunction [23]. Diquafosol treatment groups also used artificial tears to inhibit DED symptoms [11,13,23,24]. In short, neither cyclosporine nor diquafosol were solely adequate for the treatment of moderate or severe DED.…”
Section: Discussionmentioning
confidence: 99%